Understanding the Department of Homeland Security - Philpott, Don (The cabinet series, 2015)
Understanding the Department of Homeland Security discusses why the Department of Homeland Security (DHS)--the largest and the newest department of government--was established and then takes a detailed look at the role of the 22 different federal departments and agencies that were incorporated into it. DHS has more than 240,000 employees in jobs that range from aviation and border security to emergency response, from cybersecurity analyst to chemical facility inspector. Its duties are wide-ranging, but the goal is clear--keeping America safe.